A sustainability assessment of the Inxuba Yethemba local municipality - Van Lingen, Matthew (Rhodes University, Faculty of Commerce, Rhodes Business School, 2017)
The aim of this research was to assess the sustainability of the Inxuba Yethemba local municipality with the goal that policy-makers would use the assessment recommendations to improve their decision-making. The United Nations Indicators for Sustainable Development framework (3rd Edition) was chosen to carry out the assessment because of its indicator selection and methodology for distinguishing which indicators were relevant or irrelevant for the assessment (United Nations, 2007). If an indicator showed that the situation was improving, it was assumed to help with the overall sustainability of the area (Hedayati-Moghadam, Eskandar Seidayi and Nouri, 2014; and United Nations, 2007). The indicators for environmental sustainability showed that the area is on an environmentally sustainable path (Du Toit, 2017; United Nations, 2007). While the indicators for social sustainability showed that the living standards of the population (measured by poverty, housing, and access to electricity amongst others) had increased which is a good indication for social sustainability. The indicators for education and labour productivity showed the opposite (CHDM a, 2012; CHDM a, 2014; United Nations, 2007). The indicators for the economy showed that the economy was not growing which is not a good indication for economic sustainability (CHDM a, 2012; CHDM a, 2014; United Nations, 2007). The recommendation to policy-makers is that developing labour productivity through education and skills training is the most important area to improve, and compiling regular sustainability assessments will improve their decision making. Another recommendation is that, because 65% of the households rely on the social grant (CHDM b, 2014) this cannot be withdrawn in the short term. Furthermore, if inflation were to develop into hyperinflation, the value of the social grants would deteriorate (Market Insight South Africa, 2016). A recommendation to policy makers is that more data collection is needed in order to do proper sustainability assessments. Overall, the municipality cannot be classified as sustainable mainly on account of the poor education system, high levels of unemployed and unskilled labour, and the social, and economic dependence that the municipality has on government spending.
Keywords: Uncatalogued